Reflexiones en las prácticas pre profesionales en el proceso de formación universitaria en Trabajo Social desde una mirada compleja: propuestas estratégicas en los posibles encuadres de intervención y su articulación con la extensión universitaria, invest - Aguirre, Gabriela Gisela (Difusiones, 2019)
En este trabajo se propone dar cuenta de la reflexión de experiencias transitadas desde la mirada de la docencia universitaria, en el desarrollo de los espacios de prácticas pre profesionales con estudiantes de la licenciatura en Trabajo Social de FHyCS / UNJu / Argentina. Estos espacios están conformados intersectorialmente, de esta manera se trabajan los procesos de enseñanza/aprendizajes con los estudiantes para el impacto social en proyectos comunitarios. Se piensan estos espacios desde la complejidad social con la que estos escenarios presentan realidades con distintas problemáticas sociales, por lo tanto, el Trabajo Social se encuentra en la necesidad de proponer las diferentes posibilidades de abordajes, estrategias y encuadres en las intervenciones que realiza. Esto implica un desafío desde la docencia en Trabajo Social, en donde se producen tensiones entre el acompañamiento de aprendizaje hacia los estudiantes y el compromiso con las comunidades donde los mismos realizan sus prácticas, ya que no se dan de forma lineal, ni cerrada sino en permanente transformación. Por esto mismo se propone abordar estos escenarios con una lógica interdisciplinaria e inter-institucional, en el que se trabajan propuestas de extensión universitaria con el trabajo en el fortalecimiento de redes con las organizaciones, como también el compromiso con la producción del conocimiento en proyectos de investigación con finalidades en los procesos de profesionalización. Sustentándose en una metodología convergente, triangulando esquemas metodológicos cuali-cuantitativos, abordajes grupales y comunitarios. Abstract In this work, it is proposed to give an account of the reflection of experiences from the perspective of university teaching, in the development of preprofessional practice spaces with students of the Social Work degree of FHyCS / UNJu / Argentina. These spaces have an intersectorial form, in this way the learning processes are worked with the students for the social impact in community projects. These spaces are designed in accordance with the social complexity with which these scenarios present realities with different social problems, so Social Work should propose the different possibilities of approaches, strategies and frameworks in the interventions carried out. This implies a challenge from the teaching in Social Work, where there are tensions between the accompaniment of learning towards the students and the commitment with the communities where they carry out their practices, since they do not happen in a linear or closed way, but in permanent transformation. For this reason, it is proposed to approach these scenarios with an interdisciplinary and inter-institutional logic, in which proposals for university extension are worked with the work of strengthening networks with organizations, as well as the commitment to the production of knowledge in Research Projects with purposes in the professionalization processes. Based on a convergent methodology, triangulation of qualitative-quantitative methodological schemes, group and community approaches.In this work, it is proposed to give an account of the reflection of experiences from the perspective of university teaching, in the development of preprofessional practice spaces with students of the Social Work degree of FHyCS / UNJu / Argentina. These spaces have an intersectorial form, in this way the learning processes are worked with the students for the social impact in community projects. These spaces are designed in accordance with the social complexity with which these scenarios present realities with different social problems, so Social Work should propose the different possibilities of approaches, strategies and frameworks in the interventions carried out. This implies a challenge from the teaching in Social Work, where there are tensions between the accompaniment of learning towards the students and the commitment with the communities where they carry out their practices, since they do not happen in a linear or closed way, but in permanent transformation. For this reason, it is proposed to approach these scenarios with an interdisciplinary and inter-institutional logic, in which proposals for university extension are worked with the work of strengthening networks with organizations, as well as the commitment to the production of knowledge in Research Projects with purposes in the professionalization processes. Based on a convergent methodology, triangulation of qualitative-quantitative methodological schemes, group and community approaches.